A comparative study of depression between men and women - Khoshbooii, Robab; Hassan, Siti Aishah (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
Depression has become one of the primary concerns of public health. Depression is a mood disorder which is characterized by feeling of sadness, helplessness and worthlessness, as well as psychological symptoms including lack of energy, sleep cycle disturbance and appetite Changes (American Psychiatric Association, APA, 2000). It is a highly prevalent Illness which affects both men and woman disproportionately. Previous study indicates that there is a significant difference of depression between men and women. Nevertheless, to what extent does gender really matter IS yet to be examined. In addition this study also intends to investigate whether the degree of difference on depression between male and female patients are the same at the different stage of lifespan. Prelimitary analysis of the available literature indicates that women are found to be depressed as compared to men. Depending on how depression is defined and assessed, lifetime prevalence rates for diagnosable major depressive disorder range from 2.6% to 12.7% in men, and 7% to 21% for women (Kessler et al., 1994, M. Weissman, Bruce, Leaf, Florio, & Holzer, 1991) and lifetime prevalence of depression in women is consistently greater than in men. Therefore, it is practically important for the counselor and psychotherapist to give higher attention on the treatment of depression among women.